2010
DOI: 10.1111/j.1551-2916.2010.03804.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimony Tuned Rhombohedral‐Orthorhombic Phase Transition and Enhanced Piezoelectric Properties in Sodium Potassium Niobate

Abstract: It has been reported that the rhombohedral–orthorhombic low‐temperature polymorphic phase transition in (Na,K)NbO3 can be tuned close to room temperature by substituting Sb for Nb, such that enhanced piezoelectric properties are induced based on the theory of two‐phase coexistence. A diagram of phase structures changing with Sb content and temperature has been generalized for (Na,K)(Nb,Sb)O3 (NKNS) compositions. The thermal stability of piezoelectric properties of NKNS ceramics was evaluated considering the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
186
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(194 citation statements)
references
References 28 publications
6
186
2
Order By: Relevance
“…1c, d that the solid solutions are of orthorhombic symmetry when x B 0.6. The split {100} and {200} peaks become one peak when x C 0.8, confirming that the orthorhombic and rhombohedral phase coexistence can be formed [25][26][27][28].…”
Section: Methodssupporting
confidence: 70%
See 1 more Smart Citation
“…1c, d that the solid solutions are of orthorhombic symmetry when x B 0.6. The split {100} and {200} peaks become one peak when x C 0.8, confirming that the orthorhombic and rhombohedral phase coexistence can be formed [25][26][27][28].…”
Section: Methodssupporting
confidence: 70%
“…Other attempts have been made to design KNN-based ceramics with additives (BaZrO 3 , CaZrO 3 , BiScO 3 ) by shifting rhombohedral-orthorhombic phase transition temperature (T O-R ) toward room temperature [17][18][19]. This rhombohedralorthorhombic phase coexistence zone is still a polymorphic phase boundary (PPB), rather than a MPB, for its temperature dependent behavior [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, those KNNbased ceramics with Sb will be harmful to the human health because of its light toxicity, and moreover their T C will be rapidly dropped by doping Sb 5+ [32]. In addition, a pure KNN ceramic modified by (Bi,M) ZrO 3 also possesses a relatively poor d 33 [29,30].…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, the R-O phase transition temperature (T R-O ) at a low temperature has been almost neglected for the KNN system. More recently, it has been reported that the T R-O phase transition below room temperature of (Na, K) (Nb, Sb) O 3 , KNN-BaZrO 3 and KNN-BiScO 3 ceramics can be tuned close to room temperature, and better piezoelectric properties are induced by the theory of two-phase coexistence [11][12][13].…”
Section: Introductionmentioning
confidence: 98%